PENGARUH PENAMBAHAN LARUTAN H3BO3 DAN LiOH TERHADAP PERILAKU KOROSI MATERIAL KELONGSONG ZIRCALOY-2 DALAM MEDIA AIR BEBAS MINERAL - Al Afghani, Fajar; Hermawan, Erwan; Putri, Anditania Sari Dwi; Nurlaily, Ely (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
The primary coolant of the PHWR type reactor is controlled chemically by the addition of boric acid and LiOH to anticipate corrosion of the cladding material of Zr-2. This study aimed to analyze the effect of H3BO3 and LiOH solutions on the type and rate of of zircaloy-2 (Zr-2) corrosion in demineralized water. The corrosion test was carried out at room temperature to eliminate the influence of high temperature and pressure on the electrochemical process. In this study, the corrosion rate of Zr-2 was observed in a demineralized water solution with varying concentrations of H3BO3 and LiOH. The observation was done using Tafel method, where the addition of H3BO3 at concentrations of 10 ppm, 100 ppm, 500 ppm,1000 ppm and 2000 ppm resulted in corrosion rate of 17.29 x 10-3 mpy, 18. 51 x 10-3 mpy,20.82 x 10-3 mpy, 22.71 x 10-3 mpy and 23.29 x 10-3 mpy, respectively. The addition of 2000 ppm of H3BO3 and LiOH with varied concentrations of 1 ppm, 2 ppm, 3 ppm, 4 ppm results in decreasing of corrosion rate sequentially, namely 22.71 x 10-3 mpy, 21.88 x 10-3 mpy, 21.41 x 10-3 mpy, 21.39 x 10-3 mpy, whereas the addition of 5 ppm LiOH causes the corrosion rate to increase to 21.45 x 10-3 mpy. It can be concluded that the addition of LiOH and H3BO3 affects the corrosion rate of zircaloy-2 in demineralized water. Higher concentration of H3BO3 causes the corrosion rate to increase meanwhile, the addition of LiOH causes the corrosion rate to decrease to a concentration of 4 ppm. However, the addition of LiOH at a concentration of 5 ppm causes the corrosion rate to increase.